2009
DOI: 10.1111/j.1600-0765.2008.01129.x
|View full text |Cite
|
Sign up to set email alerts
|

The apical region of developing tooth root constitutes a complex and maintains the ability to generate root and periodontium‐like tissues

Abstract: The sustainable development ability of developing apical complex qualifies it as the growth center of tooth root and as a promising candidate source of cells for tooth root and periodontal regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…The strongest expression of IGF-1, IGFBP-3 and IGF-1R was evident in teeth with ongoing root development, especially in the incomplete apical base, where high proliferation and differentiation rates are normally observed (29). Furthermore, in accordance with previous studies of the potential roles of the IGF family in odontogenesis, we found that the expression of IGF-1, IGFBP-3 and IGF-1R declined when tooth development had been completed.…”
Section: Discussionsupporting
confidence: 77%
“…The strongest expression of IGF-1, IGFBP-3 and IGF-1R was evident in teeth with ongoing root development, especially in the incomplete apical base, where high proliferation and differentiation rates are normally observed (29). Furthermore, in accordance with previous studies of the potential roles of the IGF family in odontogenesis, we found that the expression of IGF-1, IGFBP-3 and IGF-1R declined when tooth development had been completed.…”
Section: Discussionsupporting
confidence: 77%
“…Many types of cells, including APCs, have been hypothesized to play roles in the regenerative processes (8,(15)(16)(17). APCs have been advocated because of their high proliferation rate and mineralization potential (18,19). An evoked-bleeding step in regenerative procedures could recruit APCs into the root canal (17).…”
Section: Discussionmentioning
confidence: 98%
“…It's well established that HERS regulates the formation of organized root dentin through epithelial-mesenchymal interactions. The absence of HERS during the formation of dentin-like structures would cause odontoblast progenitor cells to form osteodentin without organized dentinal tubules, that resembled repair dentin [15]. The mechanisms behind the osteodentin formation and odontoblastlike cells differentiation remain uncertain.…”
Section: Discussionmentioning
confidence: 99%